Transition‐Metal Nitrosyls for Photocontrolled Nitric Oxide Delivery. Issue 12 (8th February 2017) - Xiang, Hui‐Jing; Guo, Min; Liu, Jin‐Gang
Abstract : Nitric oxide (NO) is an endogenously produced biological signaling compound, involved not only in various physiological processes but also in cancer biology. The potential therapeutic applications of NO in regulation of vascular tone, anticancer, antibacterial, anti‐inflammatory, and wound healing processes has resulted in an explosion of research interest in NO donor compounds and in related materials capable of delivering NO to desired sites. Transition‐metal nitrosyls such as those of ruthenium (Ru‐NOs) are photolabile NO donors from which NO release can be manipulated on demand by application of light. This enables control of spatiotemporal delivery and of optimal NO dosage at a desired site and time. In this microreview we highlight advances of the past few years in rational ligand design, the sensitization of metal nitrosyls (especially Ru‐NOs) by use of light from ultraviolet (UV) to near‐infrared (NIR) wavelengths for efficient NO release, and integration of metal nitrosyls with various nanoplatforms for photocontrolled targeted NO delivery. Abstract : This microreview describes recent major advances in the integration of metal nitrosyls with various nanoplatforms for photocontrolled nitric oxide delivery.